Evaluation of germination characteristics of sesame cultivars (Sesamum indicum L.) seeds as related to fatty acids composition - P. Rezvani Moghaddam; S.M. Seyyedi (علوم و فناوری بذر ایران)
Oil content and fatty acid composition are the most important factors for assessing and describing oilseeds. On the other hand, seed germination and seedling establishment are affected by seed reserves. In order to investigate the germination characteristics of sesame (Sesamum indicum L.) seeds as related totheiroil content and fatty acids composition, series of laboratory and greenhouse pot experiments were conducted in Ferdowsi University of Mashhad. Experiments were arranged based on a completely randomized design with 15 treatments and four replications. The experimental treatments were consisted of 15 sesame cultivars: Darab 2, Darab 14, Dashtestan 2, Dashtestan 5, Esfaraen, IS, JL-13, Kalat, Kashmar, Mashhad, Oltan, Sistan, TS-3, Varamin 2822, and Yellow White. The results showed that the low mean germination time (MGT) and mean emergence time (MET) were detected in Dashtestan 2, Dashtestan 5 and IS cultivars. In contrast, the high MGT and MET were observed in Yellow White and Mashhad cultivars. Although, there were no statistically differences between sesame cultivars for seed nitrogen concentration and oil percentage, significant differences were observed in terms of seed phosphorus concentration. The highest and the lowest seed P concentration were obtained in Dashtestan 2 and Yellow White cultivars, respectively. There were no significant correlation between MET and fatty acids, except for oleic, linoleic and linolenic acids. A negative correlation between oleic acid and MET (R2= 0.73**) and also a positive correlation between linolenic acid and MET (R2= 0.73**) was observed. Therefore, it seems that sesame seed vigor highly depends on unsaturated fatty acids composition.